FIRST (y x 4 - y x 3 + 2y x 2 + y -1) / (y x 3 + 1)
SECOND (4y-3y+4y+y-1) / (3y+1)
THIRD (6y-1) OVER (3y+1)
Switching the hypothesis and conclusion of a conditional statement and negating both. For example, the contrapositive of "If it is raining then the grass is wet" is "If the grass is not wet then it is not raining." Note: As in the example, the contrapositive<span> of any true proposition is also true.
Therefore, the answer would be:
</span><span>If I don't spend money, then I don't have it.</span>
Answer:
208.00015
Step-by-step explanation:
Use a calculator. I'm sorry, there's no other way
Answer:
JL = 78
Step-by-step explanation:
The shorter segment is a midline, so is half the length of the longer one.
2(5x-16) = 4x +34
5x -16 = 2x +17 . . . . . divide by 2
3x = 33 . . . . . . . . . . add 16-2x
x = 11 . . . . . . . . . . divide by 3
Then segment JL is ...
JL = 4x +34 = 4(11) +34 = 44+34
JL = 78
R - 4.5 < 11
—
r would be 15.5
[ r = 15.5 ]